EMPIRICAL ENQUIRY ON THE US INCLINATION OF TRADE AND INVESTMENT WITH SPECIAL REFERENCE TO TRADE WAR AND COVID-19. - Dr. Nishant Joshi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the last few decades, the U. S-China economic ties have shown significant growth. For instance, the total U.S-China trade rose from $ 2billion to $497 billion from 1979 to 2010. Many economists and scholars argue that expanding economic ties with China have continued to expose the U.S. manufacturing firms to greater "unfair" competition from inexpensive Chinese firms. They argue that this has led to the relocation of U.S. production facilities to China, resulting in significant losses of U.S. manufacturing jobs. There have been differences in opinions of dealing with China on relevant economic issues (Crabb, 2019). The aforesaid was the major cause of the ongoing US-China Trade War and COVID-19 outbreak and US administrations firm view that China is responsible for the pandemic has only worsened already stressed trade relations under these circumstances it is imperative to study the effect of trade war and possibly how India will be score in attracting more US Trade and Investment. The paper tries to make a primary Empirical Investigation on the said issues.